Developing an Augmented Reality Learning Application for the 10 Plagues Bible Story Using the MDLC Method - Pranatania Putri Karista Rembet; Chriestie Ellyanne Clara Juliet Montolalu; Mahardika Inra Takaendengan; Christian Alderi Jeffta Soewoeh; Stephano Caesar Wenston Ngangi; Dodisutarma Lapihu (INTECH, 2026)
Sunday School learning needs interactive media that can help children understand Bible stories through concrete visual experiences. This study developed an Android-based Augmented Reality learning application for the 10 Plagues Bible story using the Multimedia Development Life Cycle method. The application was built with Unity and Vuforia and used marker-based AR to display 3D objects and animations related to each plague. Data were collected through observation, questionnaires, functional testing, technical testing, and usability evaluation. The evaluation included Black Box Testing, marker-distance testing, lighting testing, device testing, and System Usability Scale testing. The results showed that all 10 Black Box Testing scenarios were successful, indicating that the main application functions worked as designed. Marker detection worked at 15 cm and 20 cm under normal lighting. The application also ran smoothly on the tested Android devices. However, marker detection failed under dim lighting. The SUS test produced an average score of 69.79, categorized as grade D with an Ok rating. These findings show that the application is functional and usable, although improvements are still needed in user guidance, interface clarity, and low-light marker detection. The application can support Sunday School teachers in presenting Bible stories through more visual and interactive learning media.